Potential of mean force between ions in infinitely diluted simple short-range models of aqueous electrolytes - Vlcek, L.; Nezbeda, I. (Condensed Matter Physics, 2005)
As an attempt to assess the effect of the long-range electrostatic interactions
in solutions of electrolytes, a simple short-range model (SSM) of
electrolytes made up of primitive water and primitive ions (i. e., ions whose
Coulombic interaction with water has been replaced by a triangular-well
interaction) has been considered to compute the potential of mean force.
The sizes of the primitive ions have been set so as to approximate realistic
NaCl, LiI, and CsCl electrolytes. It is shown that despite the missing longrange
Coulombic interaction the model captures the basic features of real
electrolytes while the indirect, i.e. water mediated, potential of mean force
in the SSM is in qualitative agreement with that of realistic models. Обчислення потенціалу середньої сили для спрощеної моделі з
короткодіючими взаємодіями (кулонівська взаємодія між іонами
і водою замінена взаємодією трикутної ями) розглядається як
спроба визначити ефект далекодіючих електростатичних взаємодій
у розчинах електролітів. Розміри таких розчинених іонів вибирались
таким чином, щоб апроксимувати реальні NaCl, LiI, та CsCl розчини
електролітів. Показано, що, незважаючи на нехтування далекодіючими кулонівськими взаємодіями, модель відображає основні
характеристики реальних розчинів електролітів, тоді як непряма
взаємодія між іонами опосередкована водою, тобто потенціал
середньої сили якісно добре узгоджений з результатами реалістичних моделей.